Use of fungal laccases for aflatoxin reduction in maize sub-products - Bossa, Marianela (2023)
Fungal contamination is a phytosanitary problem of concern in maize and by-products. Aspergillus section Flavi strains can generate important problems due to contamination with aflatoxins (AFs). During the bioethanol production from maize, AFs levels can increase up to three times in the final co-product (DDGS or WDGS), intended for animal feed. Mosto is the milled maize grains with the addition of water and amylase enzymes that enter the fermentation stage. One strategy to reduce the mycotoxin contamination levels is the use of microorganisms or enzymes able to metabolize, destroy or inactivate those compounds. Laccases are enzymes with biocatalytic capacity and wide biotechnological application, including food industry. Particularly, laccases from fungi that cause white rot have been proposed for mycotoxin biotransformation. In the present work, the effectiveness of different fungal laccases in reducing AFs levels (AFB1, AFG1, AFB2 and AFG2) was evaluated under an in vitro assay. Laccase production by Phylum Basidiomycota strains was evaluated and 9 of them were selected to carry out in vitro decontamination tests. A concentration of 1 µg/mL of AFB1 and AFG1, and 0.25 µg/mL of AFB2 and AFG2 were used at concentrations of 5, 10, 15 and 20 U/mL of laccases contained in enzyme extracts, in addition to vanillic acid as redox mediator (1 and 10 mM). The strain Trametes sp. B7-IMICO-RC was able to degrade the 4 AFs at high levels under all the evaluated conditions. The highest degradation percentage was reached in presence of 1 mM vanillic acid and 20 U/mL laccase (88, 99, 87 and 70%, for AFB1, AFG1, AFB2 and AFG2, respectively). An additional in vitro degradation assay of AFs was carried out using mosto as the substrate. The degradation percentages observed under these same conditions were 26% for AFB1 and AFG2 and 54% for AFG1. Currently, studies are being carried out in order to determine the degradation products toxicity. These results would contribute to the development of an eco-friendly strategy to reduce mycotoxin contamination, ensuring food safety.